Effects of water aerobics on posture alignment and risk of falls of older adults: an intervention study - Camila Costa Ibiapina Reis; Marcos Antônio Pereira dos Santos; Camila Feitosa da Costa; Edna Maria Silva Araújo; Luiz Roberto Ramos (Colégio Brasileiro de Ciências do Esporte, 2021)
ABSTRACT Considering that aging leads to losses in postural control and balance, our objective was to analyze the effects of water aerobics on posture alignment and risk of falls in older adults. A quasi-experimental intervention study included 49 older adults in the Intervention Group (IG) and 34 in the Control Group (CG). A plumbed symmetrograph assessed posture alignment, while a Time Up & Go test determined the fall risk. The IG performed water aerobics twice a week for three months. Posture alignment significantly improved in most body segments assessed for the IG, and worsened in the CG. The low risk of falls in the IG increased by 28% in relation to the CG. We concluded that water aerobics improved posture alignment and reduced fall risk in older adults.